The impact of sports participation on medication costs among adolescents: ABCD growth study - von Ah Morano, Ana Elisa [UNESP]; da Silva, Jéssica Malek [UNESP]; Costa, Lara Julia Montezori [UNESP]; Osco, Karla Minacca [UNESP]; Tanganini, Beatriz Dalarme [UNESP]; Ramirez, Ariane Pereira [UNESP]; Codogno, Jamile Sanches [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Araujo, Monique Yndawe Castanho [UNESP] (Thieme, 2025)
The economic impact of physical activity has been extensively investigated among adults, but few studies have analyzed this issue in pediatric populations. To analyze the relationship of costs attributed to medicine use with the time spent in different intensities of physical activity and sports participation among adolescents. A sample of 92 adolescents were tracked for 28 weeks. The main outcome was the overall cost attributed to medicine use (assessed weekly [US$]). Independent variables were moderate-to-vigorous physical activity outside sports and sportive moderate-to-vigorous physical activity, assessed in three time points (baseline, 14 weeks and 28 weeks) using accelerometers (min/day). A total of 53 boys and 39 girls, with a mean age of 14.54 (1.96) years, were evaluated. Sedentary time (rho=0.217 [95%CI: 0.006 to 0.420]) and moderate-to-vigorous physical activity+Sportive moderate-to-vigorous physical activity (- 0.250 [95%CI:-0.447 to-0.130]) were related to costs attributed to medicine use. When the multivariate model considered sedentary time as a covariate, the relationship between moderate-to-vigorous physical activity+Sportive moderate-to-vigorous physical activity and costs attributed to medicine use became non-significant (beta=- 0.007 [95%CI:-0.017 to 0.004]; p-value=0.206). The time spent in moderate-to-vigorous physical activity was inversely related to the medication costs accumulated through the follow-up period, while sedentary time appears to counteract these benefits.